Pre Penguatan Pembelajaran PPKn berbasis digital melalui media pembelajaran Albayan di SMP: Penguatan Pembelajaran PPKn berbasis digital melalui media pembelajaran Albayan di SMP - wartono; Puji Susanti, Rini (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
This study aims to uncover the challenges and opportunities related to the use of technology in Indonesian classrooms in the digital era, meaning that the digitalization of learning media in the world of education is increasingly evident, especially in strengthening digital-based PPKn learning through Albayan learning media in junior high schools. Through the use of qualitative methods from researchers, teachers, students, and the general public to obtain comprehensive findings. All contribute to the current state of technology integration, highlighting challenges related to access to technology and infrastructure. Presenting digital and providing appropriate professional development for educators is essential to realizing the full potential of technology to advance education in Indonesia. The placement of digital content and the development of an inclusive technology-based learning environment are important elements in preparing students for a future that is increasingly dependent on technology and it is hoped that one of the initiatives in the field of Citizenship Education is the use of digital learning materials. This includes educating themselves as independent, active, critical citizens who want to participate effectively in various community, political, and government activities at all levels (national and regional); Understanding how the government implements policies, procedures, and personal responsibilities to participate in the daily lives of people at all levels (local and national); Understanding, respecting, and upholding human rights, democracy, the rule of law, and nationalism in the context of community, state, and social life. Therefore, one of the efforts to achieve and achieve citizenship competency is to downstream the development of Civic Education science that can adapt to the development and needs of learning in the era of Albayan media digitalization in learning Civic Education.